Factors influence adaptive performance among employees of manufacturing firms - Cathrine, Romas (2021)
Adaptive performance is one of the most significant topics to address in today's workplace due to covid-19. Most companies are able to meet their organizational goals. At the same time, some organizations continue to overlook how employees adapt to the new changes. The one major issue resulting from the covid-19 outbreak was the competitiveness of the organizations and it depends upon the workplace environment which got worst due to the negative impacts of covid-19 on traditional businesses. As a result of this situation, the employee may find it difficult to compete and stay afloat in the corporate sector. Adaptive performance is crucial in achieving the firm's goals and objectives. Employees’ adaptive performance is influenced by several factors, according to the researchers. The researcher has chosen employees among manufacturing firms in Kuala Ketil, Kedah as the sample of this study. The study focuses on the factors that influence adaptive performance among employees of a manufacturing firm. This study looked at influencing independent variables namely perceived organizational support, climate for innovation, employee engagement, and workplace environment to examine if there was a link between those factors and adaptive performance among employees in manufacturing firms. Questionnaires were distributed to a random employees in manufacturing firm for data collection. The hypothesis of this study shows that climate for innovation, employee engagement, and workplace environment have positively and significantly affect the adaptive performance. Employee engagement shows that it has the highest influence on adaptive performance. The perceived organizational support has not supported. In a manufacturing firm, the employee engagement factor has been found as the most important contributor to employees’ adaptive performance. Employees’ climate for innovation, workplace environment, and perceived organizational support was found to have a substantial link with adaptive performance among employees of a manufacturing firm. The future research study should be expanded to include other factors from the employees’ perspectives. The researcher may also want to identify whether the demographic factors for instance age group influence employees’ adaptive performance.